Roles of the Turats Ulama Nusantara Groups on the Counter Radicalism in Indonesia - Fathimatuz Zahra Anis (Santri: Journal of Pesantren and Fiqh Sosial, 2022)
Turats Ulama Nusantara groups are a forum for the dissemination of knowledge and the search for various studies related to Islam in the archipelago which several students pioneered. This group has an impact and color on Islamic studies. It is a pioneer in opening studies that have not been widely revealed, such as the role of Indonesian clerics in providing color for knowledge in the Arabian peninsula and many other things related to Islam in Indonesia. This article aims to look at the role of the archipelago's ulama turats who are the forum for the formation of counter-radicalism in Indonesia. This article is the result of research using qualitative research methods, based on the data and discourses that were studied in the group to be analyzed as an indication of the function of the Turats Ulama Nusantara group to function in counter-radicalism. The results of this article show the role of the Turats Ulama Nusantara group in opening discourse and knowledge that makes counter-radicalism in Indonesia.